Pengaturan Pidana Tutupan Bagi Pelaku Tindak Pidana Politik: Tepatkah? - Darryl Evan Brouwer (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
Undisclosed punishment is one of the primary penal sanctions in the Indonesian criminal law system. Criminals are imposed on perpetrators who commit criminal acts because they are driven by "respectable purpose". The element of "respectable purpose refers to political crimes. Thus, technically, convicts who are closed are given privileges compared to those convicted in prison. On the other hand, political crimes are highly destructive because they endanger the legitimate government and therefore endanger the security and peace of society. This paper seeks to examine whether undisclosed punishment is appropriate for perpetrators of political crimes. This issue is studied through a legal research method that is normative by nature with statutory and conceptual approaches. Therefore, the sources of this research are legal norms and legal doctrine which are analysed by the literature review method.  Through the legal research conducted, it can be concluded that the disclosed punishment is no longer relevant for perpetrators of political crimes because the privileges given to convicts of covertness are contradictory to the destructive nature of political crimes. In addition, the aim of social defense by criminal law will be more effectively realized by making the deterrence effect more effective, considering that political crimes are very destructive to the state and government. The author’s suggestion is that the disclosed punishment no longer needs to be regulated in Indonesian criminal law, especially the National Criminal Code.